Investigation of cis-trans photoisomerization of octyl methoxycinnamate by ATR-FTIR spectroscopy - Pattaraporn Pangnakorn (Chulalongkorn University, 2007)
Thesis (M.Sc.)--Chulalongkorn University, 2004